Manajemen Ekstubasi pada Pasien dengan Jalan Nafas Sulit Perioperatif - Adiyanto, Bowo; Jufan, Akhmad Yun; Adiyatma, Krisna Hario (Jurnal Komplikasi Anestesi, 2021)
Tracheal extubation is a critical step during emergence from general anesthesia. Good management of extubation is needed to prevent undesired complication including laryngospasm, hypoxia, airway injury. Patient with difficult airway is at risk during intubation and extubation period, so the knowledge about it is necessary.